Bridging Hospital and Community Care for Homeless Adults with Mental Health Needs: Outcomes of a Brief Interdisciplinary Intervention. (November 2018) - Stergiopoulos, Vicky; Gozdzik, Agnes; Nisenbaum, Rosane; Durbin, Janet; Hwang, Stephen W.; O'Campo, Patricia; Tepper, Joshua; Wasylenki, Don
Objective: This study examines health and service use outcomes and associated factors among homeless adults participating in a brief interdisciplinary intervention following discharge from hospital. Method: Using a pre-post cohort design, 223 homeless adults with mental health needs were enrolled in the Coordinated Access to Care for the Homeless (CATCH) program, a 4- to 6-month interdisciplinary intervention offering case management, peer support, access to primary psychiatric care, and supplementary community services. Study participants were interviewed at program entry and at 3- and 6-month follow-up visits and assessed for health status, acute care service use, housing outcomes, mental health, substance use, quality of life, and their working alliance with service providers. Linear mixed models and generalized estimating equations were performed to examine outcomes longitudinally. Additional post hoc analyses evaluated differences between CATCH participants and a comparison group of homeless adults experiencing mental illness who received usual services over the same period. Results: In the pre-post analyses, CATCH participants had statistically significant improvements in mental and physical health status and reductions in mental health symptoms, substance misuse, and the number of hospital admissions. The strength of the working alliance between participants and their case manager was associated with reduced health care use and mental health symptoms. Post hoc analyses suggest that CATCH may be associated with statistically significant improvements in mental health symptoms in the study population. Conclusions: A brief interdisciplinary intervention may be a promising approach to improving health outcomes among homeless adults with unmet health needs. Further rigorous research is needed into the effectiveness of brief interventions following discharge from hospital.